Word selection processing in Parkinson's disease: When nouns are more difficult than verbs. (March 2018) - Silveri, Maria C.; Traficante, Daniela; Lo Monaco, Maria R.; Iori, Laura; Sarchioni, Federica; Burani, Cristina
Abstract: Patients with Parkinson's disease (PD) are impaired in verb production. Interpretations range from grammatical deficits to semantic-conceptual decay of action representation. The verb production deficit in PD can also be considered a dysexecutive disorder, specifically, a deficit of selection processing during word production, due to corticostriatal damage. Producing verbs is "more difficult" than producing nouns, because verb-forms must be selected from a large set of word-forms which share the verb-root, and the set of possible verb-forms is larger than the set of possible noun-forms when a noun has to be produced. However, if we devise a condition in which a noun must be selected from a set of alternatives larger than the set of alternative forms from which a verb must be selected, we expect an opposite pattern, with nouns becoming more difficult than verbs. We used morphological tasks varying in the number of alternative responses during word production. Fourteen PD patients and 14 healthy Controls participated in the study. Participants performed a noun-from-verb ('observation' from 'to observe') and a noun-from adjective derivation task ('kindness' from 'kind'), and a verb-from-noun ('to observe' from 'observation') and an adjective-from-noun generation task ('kind' from 'kindness'). Input-stimuli were presented singularly on a screen and participants produced the response as fast as possible. Response latencies were longer in derivation tasks (several alternative responses) than in generation tasks (one possible response), irrespective of the grammatical class of the target word, with no difference between groups. PD patients were significantly less accurate than Controls only in the noun-from-verb derivation task, that is, in the task with the highest number of alternative responses (PD: 60%; Controls: 81%). Results suggest that the verb production disorder in PD patients may reflect disturbed selection processes among competitors: the higher the number of alternative responses the more severe the impairment.